Development of Primary Zn/MnO2 Battery with Cellulose-based Material - Ekdharmasuit, Panuwat; Suriyo, Kanyapak; Chueachat, Chananchida (Journal of Science Ladkrabang, 2022)
In this paper, we present the development of primary cellulose-based zinc/ manganese dioxide (Zn/MnO2) battery. The battery was fabricated using Whatman 1 paper as a cell separator. The hydrophobic and hydrophilic barriers of the electrodes were created by using painted wax. Sodium carboxymethyl cellulose (CMC) was added into electrodes as a binder to improve their performance and the separators with different thicknesses were investigated. Characterization techniques including battery cell performance test (polarization curve), electrochemical impedance spectroscopy (EIS) and current discharging with time measurement were demonstrated. It was found that the battery cell adding CMC into electrodes delivered highest cell performance. It displayed an OCV of 1.13 V and a maximum current density and maximum power density of 0.275 mA/cm2 and 0.052 mW/cm2, respectively. Additionally, the battery cell fabricated with a thin separator showed better performance due to the enhancement of OH- transportation leading to lower activation loss. These demonstrations reveal the possibility of applying cellulose into primary battery cell as an alternative low-cost and environmentally friendly power source for portable electronic devices.